ANALISIS STRUKTUR EKONOMI DAN DISPARITAS PRODUK DOMESTIK REGIONAL BRUTO ANTAR WILAYAH DI PROVINSI JAMBI - Adek Irma Rosi (LP2M Universitas Bina Bangsa, 2024)
The problem of economic development, especially related to development inequality, is an interesting issue to discuss. Gross Regional Domestic Product is one of the factors related to development inequality between regions. This research aims to analyze the economic structure and level of GRDP disparities in Jambi Province. The data used in this research is quantitative secondary data, namely GDP and population data published by government institutions, namely the Central Statistics Agency in Jambi Province. The data analysis methods used are the Klassen Typology and the Williamson Index. The results of this research based on the class typology are that there are no districts/cities that are included in the group of developed and fast-growing regions. The regions that are included in the group of developed but depressed regions are East Tanjung Jabung Regency, West Tanjung Jabung Regency, and Sungai Banyak City. The areas included in the group of fast developing regions are: Kerinci Regency, Merangin Regency, Sarolangun Regency, Batang Hari Regency, Muaro Jambi Regency, Tebo Regency, Bungo Regency and Jambi City. And there are no regions included in the group of relatively underdeveloped regions. Based on the Wiliamson Index analysis, the largest inequality was found in West Tanjung Jabung Regency with a value of 0.668, while the lowest was in Kerinci Regency with a value of 0.116